Connections: A Teaching & Learning Newsletter Vol. 2, Issue 1 - Centre for Leadership in Learning (Centre for Leadership in Learning, 2011)
Biannual newsletter of the Centre for Leadership in Learning, including: Director’s Welcome, Thinking About Teaching and Learning, Partnerships, Curriculum Notes, Teaching and Learning Strategies, SoTL News, Research Update.
Keywords: Teaching and learning; Quality assurance; Undergraduate education; Research on teaching and learning; Group work; Universal Instructional Design